STRESS ANALYSIS AND CHARACTERISTICS DUE TO THE SOUTH JAVA EARTHQUAKE, APRIL 10, 2021 - Sulastri Sulastri; Rahmat Setyo Yuliatmoko (Pusat Penelitian dan Pengembangan BMKG, 2023)
The April 10, 2021, earthquake in the south of East Java was classified as destructive. The secondary impact of this earthquake was quite significant. Many houses collapsed, and not a few casualties. This earthquake is unique because usually, destructive earthquakes occur at shallow depths, but earthquakes with a magnitude of 6.1 are classified as medium-depth earthquakes at sea. The earthquake in the south of East Java is classified as an intraplate earthquake because it is located on the continental plate, not in the plate contact area. The question is whether the damage that occurred to the building was purely due to the magnitude of the stress released by the earthquake or whether there were other factors. This study uses seismogram data for the earthquake south of East Java on April 10, 2021, with a radius (∆) of 300-1000 recorded at MEEK, MORW, and ARMA stations in Australia. It calculates the amount of stress based on the stress drop, while the stress column determines the stress mechanism. Calculation of stress drop from the source spectrum is obtained by the deconvolution method, namely the seismogram component separation technique in the form of Source (f), Path (f), Site (f), and Instrument (f). The analysis of the observed displacement spectrum used the Nelder Mead Simplex nonlinear inversion method. Meanwhile, the Stress Columb calculation was obtained using the Columb 3.3 program from the United States Geological Survey (USGS). The result of this research is that the stress drop value is 1.69 MPa, with the type of focus mechanism being a thrust fault in the sea. The earthquake in the south of East Java was caused by rock activity in the intraplate. The value of the stress drop is more significant when compared to the subduction contact area. This area is of intraplate rock with various variations, and earthquakes are rare. This study aims to analyze the stress, both the magnitude of the stress drop and the mechanism of the column stress results, so that the stress caused by the earthquake can be known and why the earthquake in the south of East Java is destructive. The quake in Southeast Java is classified as dangerous, not because of the magnitude of the stress generated or its mechanism. The damage was due to the amplification of earthquake waves in the building. The injury occurred because most of the buildings were built on soft soil, especially in several areas in East Java, such as Lumajang, Pasuruan, Trenggalek, Probolinggo, Ponorogo, Jember, Tulunggagung, Nganjuk, Pacitan, and several urban areas, namely Blitar, Kediri, Malang, and Stone. So, there is a need for earthquake disaster mitigation, especially in densely populated areas that live on soft soil. This mitigation effort is to minimize the occurrence of casualties by building buildings according to earthquake-resistant standards and avoiding development in the regions that have the potential for amplification of earthquake waves.